The relationship between workload and the mental health of nurses at the community health center - Anindia Annisa Putri; Ni Putu Emy Darma Yanti; Komang Menik Sri Krisnawati (KHD-Production, 2025)
Nurses mostly experience relatively high workloads. Excessive workloads on nurses can cause physical fatigue and affect the mental health of a nurse, thus impacting work activities for a nurse. This study aimed to determine the relationship between workload and the mental health of nurses at the Denpasar City Health Center. This type of research is correlative analytic with a cross-sectional research design. The sampling technique used in this study used the probability sampling technique with the total sampling method. The sample used was 60 respondents from the total population of all nurses at the North and East Denpasar Health Center. The research instrument used in this study for the workload variable was the NASA-TLX (National Aeronautics and Space Administration Task Load Index) instrument. In contrast, the mental health variable used the Self Rating Questionnaire (SRQ) 20 instrument. The results of this study showed that most nurses (55%) experienced heavy workloads. In comparison, the results of the mental health measurements of most nurses (80%) fell into the category of emotional mental disorders. The Spearman Rank test results obtained a p-value of 0.002 <0.05, which means that there is a relationship between the workload variable and the mental health of nurses, and a correlation coefficient value of 0.385 was obtained, which means that the correlation strength is sufficient. Excessive workload on nurses can later cause stress and burnout, ultimately affecting the nurse's mental health. Therefore, it is hoped that nurses can evaluate themselves in reducing their workload so that they can later improve their mental health to remain optimal.